Behaviour of Phosphorus in Selected Soil Types of Kerala - Vijayan A P (Department of Soil Science and Agricultural Chemistry, College of Horticulture, 1993)
In order to study the distribution of inorganic P-fractions finding suitable chemical extractant for phosphorus, to study Q/1 relationship as a method of estimating available P and for studying adsorption- desorption characteristics of the soil types of Kerala, 100 surface soil samples were collected. These soil types were selected from different parts of the state belonging to five soil types viz., laterite, coastal alluvium, brown hydromorphic, Kuttanad alluvium and black soil. It is observed that all the soil types except black soil were acidic, clay content was comparable in case of black soil, Kuttanad alluvium, brown hydromorphic and lateritic but it was very low in coastal alluvium. Maximum content of sesquioxide and total phosphorus recorded in laterite soils and minimum in coastal alluvium. Dominant inorganic fraction in laterite and black soil was Ca- P while in coastal alluvium, brown hydromorphic, and Kuttanad alluvium dominant fraction was Fe- P. Coastal alluvium recorded maximum content of saloid- P, Al- P and Fe- P content were maximum in Kuttanad alluvium. Maximum content of Ca- P was recorded in black soil. Studies in black soil showed that total P is correlated to free carbonates significantly and positively. The different extractants studied in different soils showed that extractants should be selected according to soil types. Mathew’s triacid proved as a better extractant for available P in laterite and coastal alluvium. In case of Kuttanad alluvium soil Bray No.1 is better. Mathew’s P correlated significantly to uptake in laterite, coastal alluvium and Kuttanad alluvium. Olsen’s P correlated to uptake in laterite and Kuttanad soils. Phosphate potential negatively correlated to uptake in Kuttanad alluvium, coastal alluvium and brown hydromorphic soil. Where as equilibrium phosphate potential negatively correlated to uptake in coastal alluvium alone. DPBC values are not found as a suitable method for the estimation of available P. The P desorption adsorption studies showed that adsorption studies was not correlated to P uptake. While the desorbed P correlated significantly and positively to P uptake in laterite soil alone.